2009
DOI: 10.1089/dna.2008.0778
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted Disruption of the Murine Homeodomain-Interacting Protein Kinase-2 Causes Growth Deficiency In Vivo and Cell Cycle Arrest In Vitro

Abstract: The homeodomain-interacting protein kinase 2 (HIPK2) protein is a member of a recently identified family of nuclear protein kinases that are well conserved in various organisms. HIPK2 can bind to several homeotic factors and to a series of proteins involved in the regulation of cell survival and proliferation in response to morphogenetic and genotoxic signals. Here we report Hipk2-targeted disruption in mouse; Hipk2(-/-) mice are viable and fertile but significantly smaller than their wild-type littermates. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…These findings are consistent with other studies implicating the role of Hipk2 in regulation of cell survival and proliferation 7,11,14,18,22 but are the first involving erythropoiesis specifically.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with other studies implicating the role of Hipk2 in regulation of cell survival and proliferation 7,11,14,18,22 but are the first involving erythropoiesis specifically.…”
Section: Discussionsupporting
confidence: 93%
“…Mice deficient in either Hipk1 or Hipk2 alone were initially reported to be grossly normal and fertile, 5,6 but a more recent study has shown that Hipk2 Ϫ/Ϫ mice are significantly smaller than their wild-type littermates through adulthood but show no difference in hematology, blood chemistry, or pathology. 7 Studies on the Hipk2 Ϫ/Ϫ mouse have also implicated HIPK2 in the regulation of cell proliferation and apoptosis. Survival and proliferation defects were observed in single neurons in the Hipk2 knockout, 5 and mouse embryonic fibroblasts from these mice also showed reduced proliferation with accumulation in the G 0 /G 1 phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). As already reported for other cell types (10,11), HIPK2 depletion reduced the proliferation rate of H1299 cells as shown by the reduced cell number of H1299i compared with H1299-CV control cells and by the mild increase of the G 1 phase of the cell cycle (supplemental Fig. S2).…”
Section: P27 Kip1 Repression Induced By Hipk2 Depletion Does Not Affesupporting
confidence: 82%
“…On the other hand, by phosphorylating the antiapoptotic corepressor C-terminal binding protein (CtBP) at serine 422, HIPK2 targets CtBP for proteasomal degradation and induces apoptosis even in p53-null cells (9). These events contribute to the cell response to UV, ionizing irradiation and several anticancer drugs and are impaired in HIPK2-depleted cells (10,11), suggesting a role for HIPK2 as a tumor suppressor. Indeed, there are examples of HIPK2 inactivation in human cancers such as HIPK2 mutations in cases of acute myeloid leukemia (12) or HIPK2 cytoplasmic mislocalization in breast carcinomas and in leukemogenesis (13,14).…”
mentioning
confidence: 99%